MEDIA AJAR BERBASIS INTERNET BAGI GURU BAHASA INGGRIS TINGKAT SD - Junining, Esti (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
Teaching English to young learners has become the trend in the development of education in Indonesia. Many innovative strategies have been developed to equip English teachers in developing more interesting and innovative teaching. However, the availability of the English materials are limited in the form of textbooks. This paper is intended to introduce more interesting and innovative English teaching in the form of internet – based teaching materials, which is expected to make English teaching more interactive and motivating. Some interesting materials from internet are introduced and developed to be implemented in the classroom.